2016
DOI: 10.1016/j.jare.2015.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Identification of rheumatoid arthritis biomarkers based on single nucleotide polymorphisms and haplotype blocks: A systematic review and meta-analysis

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 98 publications
0
23
0
2
Order By: Relevance
“…SNPs always show more biological significance when SNP clusters are tightly organized into haplotype blocks in the examined genomic region [28]. Association analysis with SNPLDBs increases the power of association [6,30]. In fact, compared with individual SNPs, constructed SNPLDB has a higher meaning, enhancing the accuracy and robustness of association analysis [8,11].…”
Section: Advantage Of Snpldbs For Association Analysismentioning
confidence: 99%
“…SNPs always show more biological significance when SNP clusters are tightly organized into haplotype blocks in the examined genomic region [28]. Association analysis with SNPLDBs increases the power of association [6,30]. In fact, compared with individual SNPs, constructed SNPLDB has a higher meaning, enhancing the accuracy and robustness of association analysis [8,11].…”
Section: Advantage Of Snpldbs For Association Analysismentioning
confidence: 99%
“…RA is a chronic disease associated with inflammation of the joints and the surrounding tissue, and linked with functional disability, and RA is associated in some cases with sSS as an extra‐articular manifestation. The cellular and molecular mechanisms involved in the etiology of RA have been recently a major thrust area in the worldwide research; however, it has not been established yet . Early diagnosis and assessment of its risk factors are of paramount importance towards effective management.…”
Section: Discussionmentioning
confidence: 94%
“…Sjögren's syndrome (SS) is a chronic autoimmune disease characterized by lymphocytic infiltration of the salivary and lacrimal glands , and exists as primary (pSS) and secondary (sSS), depending on whether it occurs alone, or with other connective diseases, including systemic lupus erythematosus and RA . RA is a complex disease, and both genetic and environmental factors contribute to its pathogenesis . Twin studies demonstrated that 60% of RA risk is due to inherited predisposition .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 A nivel mundial la población afectada por AR es de 1%. 3 Sin embargo, en México el 1.6% presenta esta patología. 4 Por otra parte, la periodontitis es una enfermedad crónica, inflamatoria e infecciosa de los tejidos de sostén de los órganos dentales.…”
Section: Introductionunclassified